Environmental Scenarios for the Future Nitrogen Policy in Flanders, Belgium - stijn M.M. Overloop; Dirk E.L.J. Van Gijseghem; John F.M. Helming (The Scientific World Journal)
The agricultural sector accounts for two thirds of nitrogen losses in Flanders, Belgium. Since 1991 both the government and the farmers have been taking measures to reduce the nitrogen surplus. Initially, the manure policy was aimed at distributing the manure surplus equally across Flanders. At the same time, the growth of livestock was stopped by a strict licensing policy, which required “command and control” measures. In recent years, the policy has switched to the use of individual target commitments by farmers. The Flemish manure policy will be tightened even more as a result of international pressures. An ex ante evaluation of possible policy options was carried out using three different scenarios spread out until 2010 (Business As Usual, Additional Measures, and Sustainable Development). To do this, a sector-economic, regionalized, environmental, comparative static, partial equilibrium, mathematical programming model of the Flemish agriculture was developed. The nitrogen emission into the agricultural soil was calculated by means of a regional soil balance. European targets can only be reached with manure processing, reduced fertilizer usage, and a strong reduction of intensive livestock breeding activities. The atmospheric deposition of nitrogen compounds will strongly decrease in 2010 if additional measures are taken. This will also result in a strong reduction of nitrous oxide emissions.